Nuevos registros de Solanum L. (Solanaceae) para el Bajío y regiones adyacentes - Rodríguez Contreras, Aarón; Vargas Ponce, Ofelia (Instituto de Ecología, A.C., 2001)
We report, for the first time, the presence of five species of Solanum for the Bajío and neighboring regions flora. Solanum brachistotrichum, S. hintonii, S. jamesii y S. morelliforme are grouped in Solanum section Petota while S. triquetum is part of Solanum section Dulcamara. We highlight the distinctive characteristics of each species and update their known geographical distribution. Finally, we present a drawing of S. triquetrum.